Pesantren and Social Equilibrium: A Structural Functionalist Analysis of Religious Value Clashes - Muhammad Izzul Islam An Najmi; Sulalah Sulalah; Helmi Syaifuddin; Masdar Hilmy (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
This article aims to analyze the relationship between pesantren and surrounding communities by analyzing religious value clashes through the perspective of Talcott Parsons’ structural functionalism. Existing studies on pesantren-community relations have largely focused on educational transformation, cultural adaptation, and religious authority, while limited attention has been given to understanding value conflicts as mechanisms that contribute to social equilibrium. Employing a qualitative case study approach, this research draws on in-depth interviews, participant observation, and document analysis conducted in several pesantren in East Java. The findings reveal that religious value differences emerge in areas such as educational aspirations, gender norms, technological change, and social behavior. However, these differences do not necessarily lead to social disintegration. Instead, pesantren and communities continuously negotiate competing values through dialogue, social participation, and institutional adaptation. Applying Parsons’ AGIL framework, the study demonstrates that pesantren perform adaptation through educational innovation and modernization, goal attainment through moral and religious formation, integration through community engagement and social mediation, and latency through the preservation of Islamic traditions and religious culture. This article argues that religious value clashes should be understood not as signs of dysfunction but as adaptive processes that help maintain social stability and equilibrium. The study contributes to the sociological understanding of religion by reinterpreting structural functionalism within the context of Indonesian Islam and conceptualizing pesantren as adaptive religious institutions capable of balancing tradition and social change.